Entangled Crossroads: Inter-Relationality, Masculinity, and Sex-Trafficked Boys. (January 2021) - Kepler, Christopher
In this article, I highlight systemic oppression related to identity construction and ontological performativity. I introduce the concept of inter-relationality as a discursive tool that builds upon intersectionality, feminist theology, and quantum entanglement theory. For a case study, I recount my experience observing sex-trafficked boys in Thailand in order to demonstrate the analytical model I present. My chief analytical guiding principle in the treatment of the case study is the way masculinity operates to re-enforce oppression. I propose queering masculinity using an inter-relational perspective for the purpose of de-constructing oppressive systems and replacing them with liberative ones.